A functional BCI model by the IEEE P2731 working group: data storage and sharing. Issue 3 (3rd July 2021) - Bianchi, Luigi; Antonietti, Alberto; Bajwa, Garima; Ferrante, Raffaele; Mahmud, Mufti; Balachandran, Pradeep
ABSTRACT: The IEEE P2731 working group is in the process of developing a functional model so that virtually any BCI system could be described according to it. In this paper, we want to stimulate the discussion for the definition and selection of the information that should be stored in a file for effectively allowing the sharing of BCI data and tools amongst researchers. Establishing these requirements and procedures will accelerate BCI development and lay the foundation for accessible and scalable BCI technology as well as provide the foundations for the definition of a standard file format.